2023
DOI: 10.1186/s13047-023-00651-x
|View full text |Cite
|
Sign up to set email alerts
|

How does the clinical practice of Aotearoa New Zealand podiatrists align with international guidelines for the prevention of diabetes‐related foot disease? A cross‐sectional survey

Hannah Jepson,
Peter A Lazzarini,
Michele Garrett
et al.

Abstract: Background Given the importance of preventive care for the lower limb in people with diabetes, and the absence of local guidelines in Aotearoa New Zealand (NZ), the aim of this study was to determine the alignment of assessment and management used in the prevention of diabetes-related foot disease by NZ podiatrists to the international prevention guideline recommendations. Methods A 37-item web-based survey was developed using a 5-point Likert sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The highest reported form of resource was discussion with other health care professionals. This differs from a recent AoNZ study in which podiatrists' assessment and management practices for patients with a high‐risk foot ‘often’ align with many domain items in the IWGDF guidelines [ 32 ]. Similarly, a survey of Australian podiatrists found that practitioners ‘very often’ align their practice with best practice diabetic foot management guidelines [ 33 ].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The highest reported form of resource was discussion with other health care professionals. This differs from a recent AoNZ study in which podiatrists' assessment and management practices for patients with a high‐risk foot ‘often’ align with many domain items in the IWGDF guidelines [ 32 ]. Similarly, a survey of Australian podiatrists found that practitioners ‘very often’ align their practice with best practice diabetic foot management guidelines [ 33 ].…”
Section: Discussionmentioning
confidence: 70%
“…This study has a number of strengths and limitations. Firstly, although the sample size in the current study represented a small proportion of AoNZ podiatrists currently holding an Annual Practicing Certificate (9%), the sample size is similar to a recent diabetes‐related survey involving this sample [ 32 ] and is larger than the response rates obtained in a similar survey of Australian podiatrists (8%) of all registered podiatrists) [ 33 ] and UK podiatrists (6%) of all National Health Service (NHS) podiatrists [ 15 ]. Additionally, workforce data indicates that approximately 20% of AoNZ podiatrists identified their primary work setting as diabetes podiatry [ 37 ].…”
Section: Discussionmentioning
confidence: 98%